Professional Competence Enhancement of High School Teachers through Scientific Paper Writing Training - Fanny Rahmatina Rahim; Dinovia Fannil Kher; Yulyanti Harisman (Lectura : Jurnal Pendidikan, 2023)
The study fulfils the gap in teachers' scientific paper writing skills, which benefits both the academic community and pupils. Teachers' competence can be improved so that they can engage in evidence-based practices, contribute to academics, and deliver engaging educational experiences that develop critical thinking in their pupils. Scientific paper writing training is critical for developing high school teachers' professional competency. The purpose of this study was to look into the efficiency of such training in improving teacher abilities and knowledge. A quantitative descriptive method was employed in the study to evaluate the efficiency of a scientific paper writing training programme for high school teachers. Data was gathered by assessing the quality of the teachers' papers using a quality assessment form. The data was analysed using statistical procedures such as the t-test and N-Gain analysis. The t-test compared pre- and post-treatment scores, while the N-Gain analysis assessed the training's effectiveness. These methodologies aided in determining the program's impact on teachers' writing skills and quantifying the level of development in their scientific paper writing competence. These data indicate the training program's effectiveness in improving teachers' understanding and skills in scientific paper writing. Training in scientific paper writing improves high school teachers' professional competency by increasing their understanding of article components, scholarly practices, and writing abilities. It emphasizes the importance of continuing professional growth and filling gaps in critical thinking and interdisciplinary writing.